The Global Lives of German Migrants Consequences of International Migration Across the Life Course - Erlinghagen, Marcel; Ette, Andreas; Schneider, Norbert F.; Witte, Nils.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
Based on the German case, this open access book highlights the increasing flows of migration and the internationalisation of individual life courses. It analyses the experiences of migration across four central domains - employment and income, partners and families, health and wellbeing, as well as friends and social participation - which potentially have far-reaching consequences for social inequalities and life chances. The book showcases results from an innovative probability sample that is representative of German emigrants who recently moved abroad and remigrants who recently returned from abroad and compares their international experiences with the sedentary population in Germany. Stays abroad, whether temporary or permanently, have become the new normal for increasing numbers of people from highly developed welfare states. Unnoticed from mainstream migration studies, these countries are today not only major immigration countries but also important sources of international mobility. By providing an empirically founded prism of the global lives of German migrants, this book is a valuable resource for students and researchers of migration, social inequality, and the life course and provides practitioners with insights into these regularly overlooked aspects of international migration.
Part I: Introduction -- Chapter 1. Between Origin and Destination: German Migrants and the Individual Consequences of Their Global Lives -- Chapter 2. Surveying Across Borders: The Experiences of the German Emigration and Remigration Panel Stud -- Part II: Who are the German International Migrants? -- Chapter 3. Structures of German Emigration and Remigration: Historical Developments and Demographic Patterns -- Chapter 4. Brain Drain or Brain Circulation? Economic and Non-Economic Factors Driving the International Migration of German Citizens -- Chapter 5. Comparing the Risk Attitudes of Internationally Mobile and Non-Mobile Germans -- Chapter 6. Settlement or Return? The Intended Permanence of Emigration from Germany Across the Life Course -- Part III: Employment and Social Mobility -- Chapter 7. Affluent Lives Beyond the Border? Individual Wage Change Through Migration -- Chapter 8. Social Origins of German Emigrants: Maintaining Social Status Through International Mobility? -- Part IV: Partner and Family -- Chapter 9. Migration Motives, Timing, and Outcomes of Internationally Mobile Couples -- Chapter 10. Disruption of Family Lives in the Course of Migration: $1 (BTied Migrants$1 (Band Partnership Breakup Patterns Among German (R)emigrants -- Part V: Wellbeing and Health -- Chapter 11. The Happy Migrant? Emigration and its Impact on Subjective Well-Being -- Chapter 12. Healthy Migrants? Comparing Subjective Health of German Emigrants, Remigrants and Non-Migrants -- Part VI: Friends and Social Integration -- Chapter 13. Out of Sight, out of Mind? Frequency of Emigrants$1 (BContact with Friends in Germany and its Impact on Subjective Well-Being -- Chapter 14. Emigration, Friends, and Social Integration: The Determinants and Development of Friendship Network Size After Arrival -- Chapter 15. Sense of Belonging: Predictors for Host Country Attachment Among Emigrants -- Part VII: Survey Design for Internationally Mobile Populations -- Chapter 16. Setting up Probability-Based Online Panelsof Migrants with a Push-to-Web Approach: Lessons Learned from the German Emigration and Remigration Panel Study (GERPS) -- Chapter 17. Is There More Than the Answer to the Question? Device Use and Completion Time as Indicators for Selectivity Bias and Response Convenience in Online Surveys.s
Keywords: Emigration and immigration; Life cycle, Human; Population -- Economic aspects; Human Migration; Life Course; Population Economics